« . situ autem valde inconstanti. » La représentation de l’Europe du Nord chez Abraham Ortelius (cartographie historique et dictionnaires toponymiques) - Besse, Jean-Marc (Presses universitaires de Rennes, 2019)
Sixteenth-century geography, as well as new spatial conceptions of the earthly world, developed a historical imaginary. The aim of this paper is to study the historical method and the philological work of Abraham Ortelius, and to stress his ambivalent attitude toward antiquity. The Flemish cartographer and antiquary not only published maps and atlases but also compiled huge dictionaries of ancient place-names, from the Synonymia geographica to the Thesaurus geographicus. In this paper, Ortelius’ philological and lexicographical activities and methods will be analysed from the point of view of his interest in the northern regions of Europe.